A finite element numerical simulation analysis of mine direct current method’s advanced detection under varied field sources - Xie, Haijun; Li, Wanlu; Li, Jin; Guo, Yaofan; Yan, Yu; Liu, Ruiqing; Cheng, Jinhao (Frontiers in Earth Science, 2023)
Ensuring the safety of coal mine production requires accurate forecasting of coal road heading faces in advance. Because of its high resistance to electromagnetic interference, the mine direct current (DC) method has been widely utilized in the advanced detection and prediction of coal mines. The layout of the field source significantly influences the detection outcomes obtained through this method. In this study, a variety of full-space three-dimensional geoelectric models were established based on the fundamental principle of DC resistivity, and the response features of geological anomalies located in various positions in front of a roadway were studied under different field source conditions using finite element numerical simulation. The electrical response characteristics were analyzed with the electrodes positioned in different directions and two-point to seven-point current sources located on the floor and side of the roadway, respectively. The electrical response of the geological anomalies was characterized with varying positions of the multi-point current source in the roadway and the pole distance of the power supply electrode. Furthermore, the electrical response characteristics of the mine DC method in advanced detection were compared for geological anomalies placed differently across the entire space. The results indicate that the response effect of the geological anomaly in front of the roadway is greater when the field source is placed on the shorter side of the roadway cross-section, with the number of field sources showing a positive correlation with the product of the pole distance and low-resistance amplitude. In advanced detection by DC method, the existence of geological anomalies on the side will affect the recognition of anomalies in front of the roadway.